A strengths, weaknesses, opportunities, and threats analysis– A study of Association of Community/Public Health Nursing Educators members. Issue 3 (25th October 2020) - Kuchler, Elizabeth; Garner, Linda; Whitten, LaDonna; DeBlieck, Conni; Farra, Sharon; Davis, Rebecca; Eardley, Debra; Stalter, Ann
Abstract: Objective: Aims of this study were to identify the Association of Community/Public Health Nursing Educators members' demographics, educational preparation, and research competencies; and, to complete a strengths, weaknesses, opportunities, and threats (SWOT) analysis. Methods: A descriptive‐correlational design was employed. Primary data collection was via electronic survey. Authors developed a survey focusing on demographics and aligning Benner's theory with research skills/experience. SWOT and gap analyses were performed. Results: A 27.2% response rate ( N  = 352) revealed a lack of diversity among 70% doctorally prepared membership, perceived competence with interprofessional collaboration (80%), and applying research to practice (80%). Doctorally prepared members reported experience using longitudinal designs ( p  = .05). PhD‐prepared members reported experience using psychometrics and evaluations ( p  = .05). SWOT revealed a lack of service engagement. Gap analysis offered solutions to execute strategic goals. Conclusions: Association of Community/Public Health Nursing Educators may enhance future direction by advancing member diversity, professional development, collaborative scholarship, and mentoring.